Tálim hám tárbiya túsinikleri hám onıń qatnasıwshıların sociallıq qorǵaw (SCIENCE and SOCIETY, 2022)
The article examines the social protection of the rights of participants in education, the work carried out in the Republic of Uzbeki- stan to protect their rights, and the issued regulatory legal acts.